Early Detection of Adverse Drug Events via 24-h Telephone Services in a Community Pharmacy: A Case Report - Masaki Maehara; Masayasu Sugiyama (Case Reports in Psychiatry)
A 57-year-old woman with bipolar disorder (BD) was started on combination therapy with aripiprazole and lithium. At the same time, a community pharmacist administered follow-up through 24-h telephone services for the early detection of adverse events. Four days after starting therapy, the patient called a community pharmacy after working hours and mentioned the occurrence of disabilities, possibly due to adverse effects, including extrapyramidal symptoms (EPSs), to the pharmacist who received the forwarded call. The community pharmacist immediately called the hospital to report the patient’s problems and suggested a decrease in doses or withdrawal of the suspected medications to the prescribing doctor. After several hours, the hospital called and informed the pharmacist that the doctor had instructed the patient to discontinue aripiprazole. The pharmacist immediately called the patient, explained the doctor’s instructions, and found that the EPS symptoms improved gradually, except for difficulty speaking smoothly. Ultimately, valproic acid was prescribed instead of lithium, resulting in a dramatic improvement in speech difficulties. These results indicate that community pharmacist-administered follow-up and intervention, especially through 24-h telephone services, is crucial for drug safety management, such as early detection of adverse events caused by combination therapy in patients with BD.